2018
DOI: 10.1016/j.ajhg.2018.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Bi-allelic Mutations in LSS, Encoding Lanosterol Synthase, Cause Autosomal-Recessive Hypotrichosis Simplex

Abstract: Hypotrichosis simplex (HS) is a rare form of hereditary alopecia characterized by childhood onset of diffuse and progressive scalp and body hair loss. Although research has identified a number of causal genes, genetic etiology in about 50% of HS cases remains unknown. The present report describes the identification via whole-exome sequencing of five different mutations in the gene LSS in three unrelated families with unexplained, potentially autosomal-recessive HS. Affected individuals showed sparse to absent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
102
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(115 citation statements)
references
References 41 publications
5
102
1
2
Order By: Relevance
“…A summary of cholesterol biosynthesis, including known mutations associated with hair disorders (as indicated by stars). Mutation to LSS has been associated with autosomal‐recessive hypotrichosis simplex presenting with sparse scalp hair . Mutations to EBP in Conradi–Hünermann syndrome are associated with Follicular atrophoderma and patchy scarring alopecia .…”
Section: Cholesterol Homeostasis: a Cellular Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…A summary of cholesterol biosynthesis, including known mutations associated with hair disorders (as indicated by stars). Mutation to LSS has been associated with autosomal‐recessive hypotrichosis simplex presenting with sparse scalp hair . Mutations to EBP in Conradi–Hünermann syndrome are associated with Follicular atrophoderma and patchy scarring alopecia .…”
Section: Cholesterol Homeostasis: a Cellular Overviewmentioning
confidence: 99%
“…A number of studies have also identified mutations in genes linked with cholesterol homeostasis and hair phenotypes, as shown in Table . Indeed, a recent publication employing whole‐exome sequencing identified mutations in lanosterol synthase (LSS), linked to autosomal‐recessive hypotrichosis simplex . LSS is involved in the production of lanosterol during cholesterol biosynthesis (Figure A) .…”
Section: Associations Between Cholesterol and Hair Pathologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, very recently, hypotrichosis has been reported to be an associated phenotype with biallelic LSS mutations [7,8]. Out of 24 patients, all had either cataracts (5/24) or hypotrichosis (20/24), and one had both [5][6][7][8]. Thus, cataracts and hypotrichosis are core symptoms in patients with biallelic LSS mutations.…”
Section: Introductionmentioning
confidence: 98%
“…Biallelic mutations in LSS were first reported in families with congenital cataracts [5,6]. In addition, very recently, hypotrichosis has been reported to be an associated phenotype with biallelic LSS mutations [7,8]. Out of 24 patients, all had either cataracts (5/24) or hypotrichosis (20/24), and one had both [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%